2000
DOI: 10.1111/j.1348-0421.2000.tb01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Oral Vaccination Induces Mucosal Immune Response Sufficient to Eliminate Long‐Term Helicobacter pylori Infection

Abstract: We examined the efficacy of therapeutic oral vaccination using Helicobacter pylori-whole cell sonicate and cholera toxin (CT) in mice persistently infected with H. pylori. Efficacy was determined by bacterial culture and microscopic examination of gastric tissues for the persistence of bacteria at 6 weeks after the last vaccination. Vaccination of H. pylori-whole cell sonicate combined with CT eradicated bacteria in 10/16 mice (62.5%). Interestingly, oral vaccination with CT alone also eliminated the bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 26 publications
4
32
1
Order By: Relevance
“…However, the mice were not challenged in that study and thus, the protective role of Th1 vs. Th2-type immunity was not defined. An H. pylori sonicate containing LPS, with either CT or heat-labile enterotoxin (LT), has normally been thought to induce Th2 immunity and reduce bacterial load in H. pylori vaccine studies [8,19,28]. However, in our study, we observed no reduction in bacterial load with a Th2 inducing, LPS−/CT vaccine (Fig.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…However, the mice were not challenged in that study and thus, the protective role of Th1 vs. Th2-type immunity was not defined. An H. pylori sonicate containing LPS, with either CT or heat-labile enterotoxin (LT), has normally been thought to induce Th2 immunity and reduce bacterial load in H. pylori vaccine studies [8,19,28]. However, in our study, we observed no reduction in bacterial load with a Th2 inducing, LPS−/CT vaccine (Fig.…”
Section: Discussioncontrasting
confidence: 55%
“…This observation prompted early vaccine research to focus on the induction of T helper type 2 (Th2) immunity, since it was suspected that Th1 immunity prevented clearance from the host. Though some work supported this hypothesis [8], most studies suggest that in fact a strong Th1 biased environment, including increased gastritis, may be necessary for protection and clearance [13][14][15]. H. pylori vaccine studies using IL-4 knockout and B cell deficient mice have further supported this hypothesis, demonstrating that neither IL-4 nor antibody production (Th2 responses) are necessary for protection [13,16].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…So far, no vaccine preventing H pylori infection has been commercially available. The majority of studies attempting to produce a vaccine have focused on urease enzyme, heat shock protein, and vacuolating cytotoxin [35,[48][49][50] , but rarely on H pylori flagellin. H pylori flagellin is composed of two subunits, named as FlaA with 53KDa and FlaB with 54 KDa respectively.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, oral or parenteral immunization using H. pylori whole cell sonicate (WCS) or a recombinant urease seem to be effective in preventing subsequent H. pylori infection, as demonstrated in a series of studies seeking an alternative to antibiotic therapy. Goto et al (9) reported that H. pylori WCS combined with cholera toxin (CT) effectively prevented subsequent infection by H. pylori, and Ikewaki et al (14) described the efficacy of the same formula in reducing the number of colonizing bacteria. Furthermore, Guy et al (11,12) revealed that parenteral immunization with H. pylori urease plus certain adjuvants was effective against H. pylori infection when given prophylactically as well as for therapeutic purposes.…”
mentioning
confidence: 99%